Ontogenic development of immunoglobulins (Igs)-positive lymphocytes in the lymphoid organs of native chickens of Bangladesh - Md.Zahirul Islam Khan; Md. Nabiul Islam; Mir Rubayet Jahan; Ryutaro Fujinaga (ELSEVIER, 2013)
The first appearance, distribution and frequency of immunoglobulins (Igs)-positive lymphocytes were investigated in the lymphoid organs of native chicken’s embryos from embryonic day (ED) 8 to ED 20. The tissues from the lymphoid organs were dehydrated in alcohol, cleared in xylene, embedded in different grades of paraffin and 6-micron thick sections were immunostained by the indirect immunoperoxidase method using antichicken immunoglobulins. IgM-positive lymphocytes were first identified in the follicles of bursa of Fabricius at ED 10, in the white pulp of the spleen at ED 14 and in the lamina propria of the cecal tonsil at ED 20. Their frequencies of populations were statistically significant from ED 14 to ED 20. IgG-positive lymphocytes were first appeared in the bursa of Fabricius and spleen at ED 20. In the bursa IgG-positive lymphocytes were located in the medulla and cortical part of the follicles, whereas, in the spleen these immune cells were located around the white pulp. IgA-positive lymphocytes were not observed in any of the developing lymphoid organs of the present study. When the data for bursa of Fabricius, spleen, thymus and cecal tonsil were statistically compared, it was observed that both IgM- and IgG-positive lymphocytes were significantly higher in bursa of Fabricius.